Testing of real exchange rate - real interest rate differential relationship in Serbia-EMU case - Petrović, Predrag M (Industrija, 2013)
The goal of this study is to investigate whether there are empirical proofs for sustainability of real exchange rate - real interest rate differential relation in Serbia – EMU case for the period between January 2007 and May 2012. Theoretical relation has been derived by combining uncovered interest rate parity and Fisher equation, while empirical testing has been based on time series cointegration concept and application of Johansen and Engle-Granger cointegration test. The findings we obtained have shown that real exchange rate index and real interest rate differential are not cointegrated series, i.e. that there is no long-run equilibrium relation between them. Based on such findings we can conclude that there are no empirical proofs that real exchange rate - real interest rate differential relation is a key to explain dynamics of RSD/EUR real exchange rate.